2019
DOI: 10.1007/s00431-019-03345-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blind intubation with different supraglottic airway devices by inexperienced physicians in several airway scenarios: a manikin study

Abstract: Endotracheal intubation is the gold standard for airway management. Supraglottic airway devices (SADs) are useful in airway abnormalities. SAD blind intubation enables airway management with better ventilation and a reduced risk of gastric content aspiration. The aim was to compare various SADs in blind intubation performed by inexperienced physicians in several pediatric airway scenarios. One hundred sixteen physicians with no previous experience with SAD performed blind endotracheal intubations with (1) iGEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…[20][21][22] However, the chest compression and LMA insertion time relationship remains controversial in that Bielski, et al and Lee, et al reported that there was no statistical association between chest compression and LMA insertion times, whereas Kohama, et al reported elongation of the LMA insertion times due to chest compression. [21][22][23] Inline bimanual cervical spinal motion restriction might render LMA insertion more difficult because the angle between the oral and pharyngeal axes becomes acute at the back of the tongue. 24 However, in the present study, inline bimanual cervical spinal motion restriction did not affect the first-pass success rates and insertion times.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] However, the chest compression and LMA insertion time relationship remains controversial in that Bielski, et al and Lee, et al reported that there was no statistical association between chest compression and LMA insertion times, whereas Kohama, et al reported elongation of the LMA insertion times due to chest compression. [21][22][23] Inline bimanual cervical spinal motion restriction might render LMA insertion more difficult because the angle between the oral and pharyngeal axes becomes acute at the back of the tongue. 24 However, in the present study, inline bimanual cervical spinal motion restriction did not affect the first-pass success rates and insertion times.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate intubation, as demonstrated in this case, videolaryngoscopes may be an alternative [3436], or the intubator can use a bougie stylet for difficult intubation. The second parameter that may reduce the effectiveness of intubation may be the fact that intubation is performed during resuscitation procedures, where chest compressions are implemented in parallel: moving the patient may make it difficult to visualize the vocal structures [27, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the supraglottic airway devices (SADs) are widely used as an intermediate device between facemask and endotracheal tube for administration of general anaesthesia in short surgical procedures. The second generation SADs has achieved a solid and proven place as rescue device for managing difficult airways 1,2 and as conduit 3,4 to aid endotracheal intubation. These are also frequently used as resuscitation device to secure the airway especially in the out-of-hospital emergencies.…”
Section: Introductionmentioning
confidence: 99%